2016
DOI: 10.1371/journal.pone.0155852
|View full text |Cite
|
Sign up to set email alerts
|

Histone Modification Is Involved in Okadaic Acid (OA) Induced DNA Damage Response and G2-M Transition Arrest in Maize

Abstract: Histone modifications are involved in regulation of chromatin structure. To investigate the relationship between chromatin modification and cell cycle regulation during plant cell proliferation, Okadaic acid (OA), a specific inhibitor of serine/threonine protein phosphatase, was applied in this study. The results showed that OA caused the cell cycle arrest at preprophase, leading to seedling growth inhibition. Western blotting assay revealed that the spatial distribution of phosphorylation of Ser10 histone H3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Post-translational modifications of histones can regulate ovarian follicle formation and maturation; H3K4me has roles in follicular development and embryonic viability [ 27 ], H4K5ac facilitates DDR due to its chromatin de-condensation properties [ 28 ] while H4K12ac and H4K16ac are involved in DDR by preventing RAD5-dependent CAG repeats [ 29 ]. Histone modifications reported to be involved in DNA repair include H3K4me [ 30 ], H4K5ac [ 31 ], H4K12ac [ 29 , 31 ], and H4K16ac [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Post-translational modifications of histones can regulate ovarian follicle formation and maturation; H3K4me has roles in follicular development and embryonic viability [ 27 ], H4K5ac facilitates DDR due to its chromatin de-condensation properties [ 28 ] while H4K12ac and H4K16ac are involved in DDR by preventing RAD5-dependent CAG repeats [ 29 ]. Histone modifications reported to be involved in DNA repair include H3K4me [ 30 ], H4K5ac [ 31 ], H4K12ac [ 29 , 31 ], and H4K16ac [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Modifications to histone H3 are the most-studied histone changes at present, and these changes have been associated with changes in gene expression. 10 Previous evidence has identified specific histone H3 modifications after exposure to organic chemical compounds, 11 heavy metals, [12][13][14] and, recently, traffic-related PM exposure in adults. 15 To our knowledge, no human studies have reported on prenatal air pollution exposure and its role in histone H3 modifications.…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally, it has been shown that OA can cause oxidative stress in aquatic species such as bivalves through increased reactive oxygen species (ROS) and lipoperoxidation [ 26 , 27 ]. An excess of ROS can in turn cause intracellular damage that not only affects membrane lipids, but also proteins and DNA [ 28 , 29 ]. However, the alteration of antioxidant enzyme activity will depend mainly on the concentration and route of exposure to the xenobiotic or toxins involved [ 30 ].…”
Section: Introductionmentioning
confidence: 99%